Specimen and data sharing to advance research and development on Zika virus - Peeling, Rosanna W.; Fongwen, Noah T; Guzman, Maria G; Méndez-Rico, Jairo Andres; Avumegah, Michael Selorm; Jänisch, Thomas; Lackritz, Eve M (The lancet. Microbe, 2025)
For diseases with epidemic potential, specimen and data sharing is crucial for sustained research and development of medical countermeasures such as diagnostics, therapeutics, and vaccines. In the case of Zika virus, although a global framework for specimen and data sharing to advance research and development is highly desirable, challenges related to legal, ethical, and intellectual property issues persist. Since the 2015-16 Zika virus outbreak, regional laboratory networks and research partnerships have made some progress in specimen and data sharing among some Zika virus-endemic countries. Pragmatic steps such as securing funds for augmenting laboratory capacity, building biobanks within public health laboratory infrastructures in low-income and middle-income countries, clearly defining the specimens and data that need to be collected, developing standardised protocols, harmonising data system interoperability to facilitate sharing, and defining mechanisms for benefit sharing will pave the way for timely development and deployment of medical countermeasures in public health emergencies.
Online verfügbar 27 February 2025, Version des Artikels 3 June 2025
Gesehen am 21.11.2025